UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN INDUKTIF SISWA KELAS VII A SMP N 1 BINANGUN CILACAP - Elly Setyowati (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of the study was to describe the process of inductive learning to enhance the activity and outcomes of learning mathematics for students of class VII A, SMP Negeri 1 Binangun, Cilacap. Type Classroom Action Research (CAR). Subjects were students of class VII A Binangun SMP Negeri 1 Cilacap, involving 33 students. Object of research activity and outcomes of learning mathematics using inductive learning model. The results showed an increase in the activity of the student's learning experience, from the first cycle of the average percentage of the activity of 50,21% in the second cycle becomes 73,37%. Mathematics learning outcomes also increased from an average value of 66,33 at the beginning of the ability of the first cycle to the second cycle of 71,64 and the average is 81,94. Percentage achieving KKM also increased from 51,51% in the prior knowledge, the first cycle to be 66,67% and 87,88% in the second cycle. Thus, teachers are advised to apply inductive learning model, as an alternative learning model to enhance the activity and student learning outcomes.